The Business Process Outsourcing Sector in the Philippines: A Defiant Trend - Herguner, Burak (Mediterranean Journal of Social Sciences, 2013)
In recent years, Business Process Outsourcing (BPO) sector has become the pillar of the Philippine Economy because of itscontribution in terms of employment and financial returns. This study aims to understand why the sector has a stronginternational competitiveness, even though the lack of competitiveness is generally admitted as the main hindrance for thenation to achieve its economic development. Therefore, the paper sheds light on the main sources of the sector, which fosterits international competitiveness, by employing Porter’s Diamond model to the sector. The findings of the study are vastlysupportive of Porter’s hypothesis in diamond model. The paper concludes that the sector may keep its high competitiveness atinternational level with some structural changes.